Decentralized proportional-integral sliding mode tracking control for a class of nonlinear interconnected uncertain system [UTM journal article] - Mohamad Noh Ahmad 559464; Mohd. Ruddin Abdul Ghani 175388; Johari Halim Shah Osman 432877
PSZJBL